2015
DOI: 10.1007/s13193-015-0473-1
|View full text |Cite
|
Sign up to set email alerts
|

Male Breast Cancer in India: Series from a Cancer Research Centre

Abstract: Male breast cancer (MBC) is an uncommon malignancy. The scarcity of cases has reduced the focus of research in this area as compared with female breast cancer. The incidence of breast cancer in males is slowly rising and it becomes important to study the biology of this uncommon illness. Aim of the present work was to study the clinico-pathological behaviour of male breast cancer at a cancer research institute in India. 18 cases of MBC were identified out of 1752 cases of breast cancer registered during a 10 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
22
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 14 publications
6
22
2
Order By: Relevance
“…[ 1 2 ] We have summarized the data on available Indian series on male breast cancer [ Table 3 ]. [ 4 5 6 7 8 9 10 11 ] Clinical and demographic finding are in concordance with the reported Indian series. Most studies show that male breast cancer presents in an advanced stage while most of our patients were in early stage.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…[ 1 2 ] We have summarized the data on available Indian series on male breast cancer [ Table 3 ]. [ 4 5 6 7 8 9 10 11 ] Clinical and demographic finding are in concordance with the reported Indian series. Most studies show that male breast cancer presents in an advanced stage while most of our patients were in early stage.…”
Section: Discussionsupporting
confidence: 88%
“…[ 3 ] Literature pertaining to male breast cancer is sparse, particularly in our country. [ 4 5 6 7 8 9 10 11 ] The present study was done with an aim to analyze the clinicopathological and survival characteristics of male breast cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted by Rai et al, [12] from North India, revealed the incidence of MBC as 0.5% while Shah et al [13] have reported a relatively high incidence of 4.1% from Kashmir. In our study, the prevalence of MBC in this study was 1.34%, among all MBC cases and 2.50%, among all breast lesion which is similar to the study conducted by Sundriyal et al [14] and Mitra et al [15] The prevalence of MBC increases with age. Age frequency distribution for males is unimodal with a peak incidence in the late sixth and early seventh decade.…”
Section: Discussionsupporting
confidence: 90%
“…[4] The diagnostic evaluation and staging system used for MBC are the same as for female breast cancer, but MBC exhibits more frequent lymph node involvement, more frequent lymphovascular invasion and advanced stages than in females. [14,22,29] It probably due to paucity of breast tissue in males. [30] In this study, 1 (2.7%) had Stage II, 14 (51.85%) had Stage III, and 7 (25.92%) had Stage IV, which is similar with the previous study conducted by Chikaraddi et al [2] Men with lymph node involvement have a 50% higher risk of death than those without lymph node involvement.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] Median age was 62 years (range 32-91 years) in a Moroccan study. 9,10 Similarly in our study the median age was 57 years (range 41-76 years). Poor prognosis, is seen especially in the younger age group, because most breast enlargements in young men are ignored as gynecomastia.…”
Section: Discussionsupporting
confidence: 74%